Towards Gender Equality in the Music Industry: Education, Practice and Strategies for Change - Strong, Catherine; Raine, Sarah (Bloomsbury Publishing USA, 2019)
Gender inequality is universally understood to be a continued problem in the music industry. This volume presents research that uses an industry-based approach to examine why this gender imbalance has proven so hard to shift, and explores strategies that are being adopted to try and bring about meaningful change in terms of women and gender diverse people establishing ongoing careers in music. The book focuses on three key areas: music education; case studies that explore practices in the music industry; and activist spaces. Sitting at the intersection between musical production, the creative industries and gender politics, this volume brings together research that considers the gender politics of the music industry itself. It takes a global approach to these issues, and incorporates a range of genres and theoretical approaches. At a time when more attention than ever is being paid to gender and music, this volume presents cutting edge research that contributes to current debates and offers insights into possible solutions for the future.
Google-Books-ID: DV62DwAAQBAJ
Keywords: Music / Business Aspects; Music / Philosophy & Social Aspects; Social Science / Gender Studies; Social Science / Women's Studies

The Changing Roles of Female Visual Artists in Morocco - El Azhar, Samir (Journal of Global Initiatives: Policy, Pedagogy, Perspective, 2019)
Keywords: Myriam

Le #moiaussi de la danse - Lauzon, Véronique (2019)
Des acteurs du milieu de la danse brisent le silence sur les abus de pouvoir, le harcèlement psychologique et les agressions sexuelles vécus. Deux ans après #moiaussi, une quinzaine d’entre eux tentent de faire éclater l’omerta qui plombe cet environnement jugé toxique.
Keywords: Bibliographie; Nettoyer

Les abus et la «loi du silence» dans la danse - Morneau, Caroline (Le Journal de Québec, 2019)
Abus psychologiques, physiques, sexuels: après les milieux du cinéma et de l’humour, on réalise que celui de la danse comporte son lot de scandales.
Keywords: Bibliographie; Nettoyer

Mapping the Stage Differently: Theatre #MeToo Movement and Internet Culture in South Korea - Yoon, Soo Ryon (Gender IT : Feminist reflexion on Internet policie, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Winnipeg comedy club defends decision to book Louis C.K. despite sexual misconduct - Caruk, Holly (CBC News, 2019)
An American comedian and actor who admitted to sexual misconduct will take the stage at a Winnipeg comedy club next week but not everyone is lining up for tickets.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Rhetorical Constellations and the Inventional/Intersectional Possibilities of #MeToo - Bloomfield, Emma Frances (Journal of Communication Inquiry, 2019)
Publisher: SAGE Publications Inc
Keywords: Bibliographie; Nettoyer

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Counting the music industry: the gender gap - Bain, V (Counting the music, 2019)

Politique de prévention et d’intervention contre l’intimidation, le harcèlement et la violence - École nationale de cirque - Montréal (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

“Sorry Not Sorry”: Apologizing in the Wake of #MeToo - MacArthur, Michelle (Canadian Theatre Review, 2019)
This article explores what it means to apologize for misconduct in the #MeToo era through three examples from the Canadian theatre industry: a private apology (Randolph College for the Performing Arts), a public apology (Citadel Theatre), and an absent apology (Soulpepper Theatre). Understanding a public apology as a performative utterance meant to restore a community’s trust, this article suggests the importance of examining the paratexts generated by and around it that help it achieve its function. From policy revisions, to media interviews, to public forums, these materials and events are crucial in the meaning-making process in which a #MeToo apology is engaged, especially when the theatre community’s access to the apology itself is limited. The article concludes by situating its case studies in relation to issues of misconduct in theatre education and training institutions.
Keywords: #MeToo; #SorryNotSorry; Bibliographie; Canadian theatre; Citadel Theatre; Nettoyer; Randolph College for the Performing Arts; Raphaël; Soulpepper Theatre; public apologies

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - Gürkan, Hasan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Irina

Climat toxique dans le milieu de l’humour, malaises en conférence de presse - Piqueur, Lucie (Urbania, 2019)
Le regroupement « Pour les prochaines » souhaite en finir avec la culture du viol en humour, mais c'est pas gagné.
Keywords: Bibliographie; Nettoyer

Pour les prochaines dénonce une culture toxique en humour - Ruel-Manseau, Audrey (La Presse, 2019)
Des humoristes de la relève affirment que le milieu de l’humour reste gangréné par la culture du viol, même deux ans après le mouvement mondial #moiaussi. En mettant sur pied Pour les prochaines, les jeunes femmes souhaitent « éradiquer » les inconduites sexuelles de l’industrie, et tendent la main aux acteurs importants du monde comique afin qu’ils s’allient pour poser des actions concrètes.
Keywords: Bibliographie; Nettoyer

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Keywords: Bibliographie

Formation sur le respect en milieu du travail (2019)
Cette session d’information au sujet de milieux de travail respectueux explore les raisons derrière l’augmentation du nombre de problèmes de comportement en milieu de travail, de son impact, ainsi que de l'importance de définir les attentes en matière de comportement afin d'aider les employeurs et les organismes à gérer, contrôler et prévenir les comportements pouvant constituer du harcèlement (harcèlement sexuel, discrimination, intimidation et violence ).
Keywords: Bibliographie; Nettoyer

Tackling gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, Sam (International Journal of Cultural Policy, 2019)
Cross-disciplinary research has highlighted the persistence of gender inequalities across music scenes. However, the way in which cultural policy shapes responses to gender inequalities in music has been relatively underexplored. This article draws on research from Swedish and UK contexts, supporting analysis with reference to 9 key-stakeholder interviews from both. Comparing perspectives from ‘more’ and ‘less’ gender-equal contexts, with sufficiently different cultural policy traditions, the article explores how responses to gender inequalities in music are influenced by ‘cultural democratic’ and ‘arm’s length’ approaches. It demonstrates that, as a result of these traditions, there is a comparatively more interventionist approach in Sweden at a national level, whereas the lack of central government response in the UK has encouraged more market-oriented solutions. It suggests that this ‘arm’s length’ approach necessitates different grassroots organisational strategies in order to affect change but notes that these, alongside austerity agendas, are insufficient in the long term.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2017.1341497
Keywords: Music policy; arm’s length; gender inequalities; interventionist; market-oriented

Harcèlement en milieu de travail dans les arts : à l'intention des employeurs - CulturalHRC (2019)
Une ressource de formation pour les employeurs et les conseils d’administration produite par Williams HR Consulting. Cette ressource de formation en gestion d’une durée de 30 minutes expliquera comment répondre aux allégations de harcèlement et sera accompagnée d’un questionnaire afin d’évaluer le degré de rétention.

Harcèlement en milieu de travail dans les arts : à l’intention des travailleurs culturels - CulturalHRC (2019)
Une ressource de formation pour les artistes/travailleurs culturels/employés produite par Williams HR Consulting. Cette ressource de formation d’une durée de 30 minutes démontre les actions à prendre lorsqu’ils sont victimes ou témoins de harcèlement et sera accompagnée d’un questionnaire afin d’évaluer le degré de rétention.

Sex Worker Resistance in the Neoliberal Creative City: An auto/ethnography - Tigchelaar, Alex (Anti-Trafficking Review, 2019)
Sex workers are subjects of intrigue in urban and creative economies. Tours of active, deteriorating, or defunct red-light districts draw thousands of tourists every year in multiple municipalities around the world. When cities celebrate significant anniversaries in their histories, local sex worker narratives are often included in arts-based public offerings. When sex workers take up urban space in their day-to-day lives, however, they are criminalised. Urban developers often view sex workers as existing serviceably only as legend. A history of sex work will add allure to an up-and-coming neighbourhood, lending purpose to its reformation into a more appropriately productive space, but the material presence of sex workers in these neighbourhoods is seen as a threat to community wellbeing and property values. This paper considers how sex workers, continuously displaced from environments they have carved out as workspaces, may use the arts to draw attention to these ongoing contradictions. It investigates how sex workers may make visible the idiosyncratic state of providing vitality to a city’s history while simultaneously being excluded from its living present. Most critically, it suggests ways in which sex workers may encourage those involved as producers and consumers of neoliberal urban revitalisation projects to connect these often fatal paradoxes to the laws that criminalise their labour.
Keywords: Bibliographie; Nettoyer

Female Brass Musicians Address Gender Parity, Gender Equity, and Sexual Harassment: A Preliminary Report on Data from the Brass Bodies Study - Schmalenberger, Sarah; Maddox, Patricia (Societies, 2019)
The Brass Bodies Study is an exploratory cross-sectional study designed to describe and understand the experience of female brass players. This report discusses selected data from close-ended and open-ended responses to questions regarding gender equity, parity, and sexual harassment within a web-based survey that launched the first phase of the study. The survey queried subjects’ physical changes to their brass playing due to various catalysts: life-cycle events; injury, illness, harassment, mental health, racism, and homophobia. The survey instrument further queried whether subjects received support about these changes and the effectiveness of support. The following report discusses survey responses to questions about gender parity and changes to brass playing due to sexual harassment. Additional qualitative data were generated from open-ended questions in the survey and were qualitatively coded and thematically presented to supplement the descriptive statistics provided. The information presented explores and defines salient items and themes of a population that is under researched with the hopes of generating hypotheses for continued research.
Number: 1 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Brass Bodies Study; Myriam; female brass players; female musicians; music workplace climate

Consentability: Consent and its Limits - Kim, Nancy S. (Cambridge University Press, 2019)

Violence in the mosh pit: assault within the Australian punk scene - Barnes, Ash; White, Rob (Current Issues in Criminal Justice, 2019)
The mosh pit is a unique crowd formation where audience members dance aggressively to engage with the music, the performers and each other. However, in this space, Australian punks may experience violations of bodily integrity. Multiple levels and types of transgression occur, as members break with mosh pit ethics by engaging in unwanted and unlawful sexual and physical violence. This case study provides an example of how group normative behaviour is confounded in liminal spaces – how transgression within such spaces undermines the supposed freedom experienced by its participants. Whilst the mosh pit is perceived to be a site governed by its own particular ethics, some defy these in word and practice. The rules of engagement are ambiguous, and offenders are able to rationalise their harms through neutralisation techniques and the diffusion of blame and responsibility. The consequence is that more often than not, offenders can use the unique physical nature of the mosh pit to execute personal vendettas and engage in intentional violence such as ‘crowd killing’ and sexual assault, with little social and legal consequence. Moreover, a certain culture of denial permeates participant responses to these issues. Throughout it all, the violence occurring has a decidedly masculine basis, reflecting overarching gender differences in interpersonal violence generally.
Publisher: Routledge _eprint: https://doi.org/10.1080/10345329.2018.1556281
Keywords: assault; cultural criminology; denial; mosh pit; punk scene

Women composers’ use of online communities of practice to build and support their careers - Hennekam, Sophie; Macarthur, Sally; Bennett, Dawn; Hope, Cat; Goh, Talisha (Personnel Review, 2019)
Purpose The purpose of this paper is to examine women composers’ use of online communities of practice (CoP) to negotiate the traditionally masculine space of music composition while operating outside its hierarchical structures. Design/methodology/approach The authors employed a mixed methods approach consisting of an online survey (n=225) followed by 27 semi-structured in-depth interviews with female composers to explore the concept and use of CoP. Content analysis was used to analyze the survey responses and interpretative phenomenological analysis was used to interpret respondents’ lived experiences as relayed in the interviews. Findings The findings reveal that the online environment can be a supportive and safe space for female composers to connect with others and find support, feedback and mentorship, increase their visibility and develop career agency through learning and knowledge acquisition. CoP emerged as an alternative approach to career development for practicing female music workers and as a tool which could circumvent some of the enduring gendered challenges. Originality/value The findings suggest that online CoP can have a positive impact on the career development and sustainability of women in male-dominated sectors such as composition.
Publisher: Emerald Publishing Limited
Keywords: Career progression; Communities of practice; Creative industries; Gender; Mixed methodologies; Myriam; Women composers; music industry

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Publisher: Cambridge University Press
Keywords: Arts; Myriam; admiration; condonation; epistemic injustice; honor; silencing

Antifeminismes et masculinismes d'hier et d'aujourd'hui - Bard, Christine; Blais, Mélissa; Dupuis-Déri, Francis (Presses universitaires de France, 2019)
Antiféminismes et masculinismes d'hier et d'aujourd'hui . Aussi ancienne que les lunes féministes, l'opposition à l'émancipation des femmes est loin de n'être que le reliquat d'un passé révolu : l'anti-féminisme contemporain reste vivace et pluriel. « Printemps des pères », « Manif pour tous », « célibataires involontaires » et mobilisations contre la « théorie du genre » : il est renouvelé par des masques séducteurs, des emprunts au discours égalitaire, par un répertoire d'action actualisé et par une nouvelle militance, dite masculiniste, dans un climat politique et social propice à son extension. Pour être compris et combattus, les antiféminismes doivent aujourd'hui être situés dans une perspective historique. Leur ancrage conservateur est souligné, mais aucune famille politique - ni aucune religion - n'est immunisée. Ils ne sont pas, non plus, le monopole des hommes. En analysant diverses expressions de l'antiféminisme depuis le XIXième siècle, les contributions à cet ouvrage démontrent la vitalité historique de ce combat et mettent en évidence ses points de contact avec l'homophobie et le racisme : l'intersectionnalité des haines. L'ensemble constitue une réponse inédite en même temps qu'un appel à la vigilance.

The Role of Rape-Supportive Attitudes, Alcohol, and Sexual Arousal in Sexual (Mis)Perception: An Experimental Study - Benbouriche, Massil; Testé, Benoit; Guay, Jean-Pierre; Lavoie, Marc E. (Journal of Sex Research, 2019)
While sexual misperception does not irrevocably lead to sexual aggression, it remains a significant risk factor. The present study investigated the effects of rape-supportive attitudes, alcohol, and sexual arousal on sexual perception. We used a 2 × 2 between-participants factorial design to randomly assign 135 men from the general population to a condition with or without alcohol (blood alcohol concentration target of .08%) and to a condition with or without sexual arousal. Participants were asked to listen to an audiotape depicting a sexual interaction between a man and woman and to indicate if and when they believed the woman was no longer interested in having sex. Results, obtained through survival analyses, indicate that the effects of rape-supportive attitudes on sexual misperception are moderated by alcohol consumption. Alcohol appears to be an important situational factor for activating men's implicit theories. Our study sheds new light on the role of knowledge structures in sexual perception: It identifies when, as well as suggesting how, rape-supportive attitudes may disturb sexual perception and ultimately lead to sexual misperception.
Keywords: Adult; Alcohol Drinking; Arousal; Attitude; Female; Humans; Male; Rape; Refusal to Participate; Sexual Behavior; Survival Analysis; Tape Recording; Young Adult

Harcèlement en milieu de travail dans les arts : à l'intention des employeurs (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement en milieu de travail dans les arts : à l’intention des travailleurs culturels - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Le harcèlement en milieu de travail au Québec - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Trousse à outil pour la gestion des ressources humaines : Harcèlement et violence dans le milieu de travail - Conseil des ressources humaines du secteur culturel. (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer

Le boys club - Delvaux, Martine (Les Éditions du remue-ménage, 2019)
OCLC: 1158938839

Le boys club - Delvaux, Martine (Les Éditions du remue-ménage, 2019)
Ils sont tournés les uns vers les autres. Ils s'observent et s'écoutent. Ils s'échangent des idées, des armes, de l'argent ou des femmes. Dans cet univers clos réservé aux hommes, le pouvoir se relaie et se perpétue a̧ la façon d'une chorégraphie mortifère. Le boys club n'est pas une institution du passé. Il est bien vivant, tentaculaire: État, Église, armée, université, fraternités, firmes – et la liste s'allonge. À la manière d'une chasse à l'image, c'est dans les représentations au cinéma et à la télévision que Martine Delvaux le traque. Véritable plongée en eaux noires, ce livre nous invite á considérer l'entre-soi des hommes comme un phénomène régressif. Un dispositif à profaner, déconstruire, refuser, parce que nos vies comptent

Experiences and perceptions of gender in the Australian music industry - Fairlamb, Hannah Mary; Fileborn, Bianca (Perfect Beat, 2019)
This article reports results from an online survey (n=207) about experiences and perceptions of gender from those working in the Australian music industry. Taking a feminist approach, theory on gender and hegemonic masculinity is used to discuss power in a gendered context in this industry. Literature shows women and girls experience a range of difficulties in the music industry worldwide, such as negative assumptions about their skill levels. The small body of research on gender and the Australian music industry has discussed topics such as the forgetting of women in Australian popular music history. Results reported in this article show that women’s worst experiences most often related to sexual violence or unwanted sexual advances; and men’s most often related to money. Findings contribute to the field by providing gendered analysis of self-reported data in an under-researched industry.
Keywords: Australia; gender; music; music industry; popular music; sexual harassment

Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events - Fileborn, B.; Wadds, P.; Barnes, A. (2019)
Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events
Keywords: Camille

#MeToo and the politics of social change - Fileborn, Bianca; Loney-Howes, Rachel (Palgrave Macmillan, 2019)

Safety, sexual harassment and assault at Australian music festivals: final report - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (2019)
Keywords: Camille

Étude sur la rémunération des travailleurs culturels au sein des organismes artistiques et culturels québécois - Groupe-conseil Solertia (Groupe-conseil Solertia, 2019)

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - G&#252, Hasan; rkan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Publisher: Scientia Kiadó
Keywords: Myriam; Turkey; film industry; gender; gender role; women

The power of abuse - Harvie, Jen (The Routledge Companion to Theatre and Politics, 2019)
Following revelations about sexual abuse in theatre and other entertainment industries in autumn 2017, this chapter explores the conditions which allow or
Keywords: Bibliographie; Nettoyer; Raphaël

On peut plus rien dire: Militantisme à l'ère des réseaux sociaux - Lussier, Judith (Cardinal, 2019)
Consacrée par la sous-culture web, l’expression « Social justice warrior » désigne des militants nouveau genre qui semblent s’offusquer pour un rien et ne ratent aucune occasion de saisir leur clavier pour le clamer haut et fort. Ultra réactifs, ils usent de leur voix sur les réseaux sociaux pour s’attaquer aux discours qu’ils considèrent comme racistes, misogynes, spécistes ou encore classistes. Hypersensibles ou acharnés, héros ou bourreaux : qui se cache derrière la caricature? Qu’est-ce qui les motive, et surtout, comment leur démarche s’inscrit-elle dans un projet de société au 21e siècle?Directement concernée par l’appellation, Judith Lussier se plonge au cœur du phénomène, questionne ses limites et part à la rencontre de ces individus qui ont tellement à cœur de défendre leurs idéaux de justice sociale qu’ils finissent parfois par s’en rendre malades.

Institutional Responses to #MeToo: A Conversation - Mengesha, Weyni; Dreyer-Lude, Melanie; Clarke, Kristian; Shaw, Kathryn; Warwick, Jacqueline; Palmer, Alisa; Dubois, Frédéric (Canadian Theatre Review, 2019)
Theatre administrators, artistic directors, and heads of programs from across Canada have a conversation about how institutional policies and cultures have shifted in the wake of #MeToo. The conversation features Kristian Clarke, Executive Director of the Dancer Transition Resource Centre (DTRC); Frédéric Dubois, Director of the French Section, National Theatre School; Melanie Dreyer-Lude, Chair of the Department of Drama at the University of Alberta; Weyni Mengesha, Artistic Director of Soulpepper Theatre; Alisa Palmer, Artistic Director of the English Section, National Theatre School; Kathryn Shaw, Artistic Director of Studio 58 at Langara College; and Jacqueline Warwick, Director of the Fountain School of Performing Arts, Dalhousie University. The participants reflect on the challenges of taking stock of the impacts and effects of a cultural movement that is still unfolding and the ways in which #MeToo has changed the relationship between training institutions and the performing arts industry.
Publisher: University of Toronto Press
Keywords: #MeToo; Bibliographie; Nettoyer; Raphaël; intimacy coaching; performing arts industry; sexual harassment policy; theatre training

Creating Space for Gender Diverse Theatre - Meredith, John; Levine, Sloth; Gender Explosion Working Group (StageSource, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Masculinity after #MeToo in Mainstream Theatre - Mignon, Eloïse; Rae, Paul (Performance Research, 2019)
Keywords: #MeToo; Arthur Miller; Bibliographie; Geoffrey Rush; King Lear; Nettoyer; Raphaël; Sarah Kane; masculinity; theatre

Code de Conduite pour les arts de la scène au Canada - Milieux de travail respectueux dans les arts (2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

Carefree or Controlled? Understanding the Night-Time Economy - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
The term ‘Night-Time Economy’ was coined in the late twentieth century (Shaw 2014) in town planning circles, and increasingly used into the twenty-first century to describe the expanding number of pubs, bars and clubs concentrated in city centres and targeting predominantly 18–24-year-olds (Roberts 2006: 332). But what exactly is the Night-Time Economy, and what role does it play in the lives of young women today? How has it changed as a site of leisure, and what does it mean to say that neoliberal forces have played a role in shaping it? What do we mean by the supposed ‘feminisation’ of the NTE, and what are the implications of this process for the ways that women engage with these spaces? This chapter charts the development of the NTE in the UK and the rise of the ‘24-hour city’, highlighting the ways in which neoliberal ideals have shaped both the landscape of the NTE and the types of behaviours and consumption practices that are expected within it. Such considerations are important for research that attends both to the wider social structures within the NTE and the individual specificities of the lives of young people as they participate in it. I will then explore the significance of space and place in research focusing on the NTE, situating the current study geographically and exploring Newcastle’s own NTE in more depth and detail.
Keywords: Charvis; Essex Girl; Geordie; Night-time Economy; Northern Identity

Conclusion - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As has become increasingly evident throughout this book, the girls’ night out clearly offers specific and nuanced ways in which to do femininities and friendships which are not present in other types of night out, and perhaps also specific types of pressures to do femininity. Whilst the NTE is increasingly recognised as a useful avenue through which to research young people’s lives, less attention has been given to the girls’ night out as a specific type of engagement with the NTE that may illuminate nuances in the ways in which young women ‘do’ gender and femininities. This book thus marks a unique contribution within a wider body of research on young people’s drinking and clubbing. This concluding chapter will pull together the main arguments outlined throughout this book, highlighting the tensions and contradictions embedded in young women’s negotiations of femininity and the ways in which these reflect the idea that the successful embodiment of ‘girly’ and ‘girliness’ is simultaneously something that is desired yet derided.
Keywords: Drinking Practices; Girly Girl; Research Young People; Time Girls; otheringOthering

Introduction - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
‘Going out’ is widely recognised as a central leisure activity in the lives of many young people (Chatterton and Hollands, Urban nightscapes: Youth cultures, pleasure spaces and corporate power. Routledge, 2003; Waitt et al., ‘The guys in there just expect to be laid’: Embodied and gendered socio-spatial practices of a ‘night out’ in Wollongong, Australia. Gender, Place & Culture, 18(2), pp. 255–275, 2011), and engaging in leisure practices in the Night-Time Economy (NTE) is likely to be an important part of women’s lives in the UK. Indeed, the ‘night on the town’ is framed in many research accounts as offering important opportunities for young women to relax, socialise with friends and escape from the often mundane realities of everyday life, work and other responsibilities (Guise and Gill, ‘Binge drinking? It’s good, it’s harmless fun’: A discourse analysis of accounts of female undergraduate drinking in Scotland. Health Education Research, 22(6), pp. 895–906, 2007; Jayne et al., Emotional, embodied and affective geographies of alcohol, drinking and drunkenness. Transactions of the Institute of British Geographers, 35(4), pp. 540–554, 2010). Yet, young women’s experiences of the NTE are also clearly shaped by neoliberal and gendered expectations around consumption, body work and self-regulation. In particular, it is important to explore in more depth how—within a supposed ‘post-feminist’ context—expectations around ‘appropriately’ feminine dress and behaviour may continue to shape the experiences of young women like Nicole in contemporary leisure spaces. But what does it actually mean and look like for young women to be ‘feminine’ today? Is this something that is relevant or important to them? How are tensions around girliness and femininity lived and negotiated in practice in women’s everyday lives? And crucially, is it still more difficult for some women to adopt ‘appropriately’ feminine identities than others? This book considers these questions and explores the ways in which women’s participation in the UK NTE continues to be constrained in a supposedly post-feminist society (Harris, Jamming girl culture: Young women and consumer citizenship. In A. Harris (ed.) All about the girl: Culture, power and identity. Routledge, 2004).
Keywords: Contemporary Femininity; Contextual Expectations; Feminine Identity; Night-time Economy (NTE); Nightlife Scene

‘It’s Girl Time’: Girliness and Friendships - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
With what Chatterton and Hollands call the ‘ritual descent’ (2002: 95) of young women into bars and clubs every weekend, we must take seriously young women’s participation in such spaces and explore further what role participating in the NTE plays in young women’s lives. Participating in the NTE has been increasingly recognised as an important component of the lives of many young women (Hollands 1995), and the participants in my study were no exception. Set against a backdrop of conflicting debates positioning the NTE as simultaneously a site of both pleasure and regulation, it is important to understand the value engaging with the NTE has for young women and the ways in which this can offer opportunities for ‘doing’ femininities or girliness and cementing friendships within these spaces. The girls’ night out represents a discreet and distinctive mode of engagement with the NTE, yet one that has received little attention in research, despite the fact that it is likely to reveal a huge amount about the individual and collective production and negotiation of femininities and friendships in nightlife venues. This chapter provides the backdrop for the remainder of the book by exploring what the girls’ night out means to young women and the central role it can play in the negotiation and maintenance of friendships and in doing ‘girly’. Whilst previous research has depicted friendships within the NTE as potentially shallow or instrumental and consumption practices as highly individualised, this chapter highlights the ways in which going out was described as an important and valued opportunity to maintain close female friendships, spend time together and enjoy opportunities to socialise and relax. I will also introduce some of the ways in which alcohol consumption was central to the young women’s negotiations of the NTE. Drinking could take on a particular role on the girls’ night out, where alcohol could function in the maintenance and cementing of friendships and the creation of intimacy (particularly when ‘pre-drinking’ at home). Consuming certain types of alcohol could also enable ‘girliness’ to be embodied in particular ways through certain consumption choices. I argue that the ‘girling’ of drinking and clubbing is particularly significant because alcohol consumption in public spaces has traditionally been recognised as a masculine pastime, rendering drinking and femininity fundamentally incompatible. If young women are able to rupture the linkages between public drinking and masculinity, they may be able to recast women’s presence and alcohol consumption in the contemporary NTE as feminine and respectable. I also explore the ways in which getting ready for a girls’ night offered further opportunities to do girliness collectively.
Keywords: Female Friends; Girlhood; Girly Girl; Time Girls; wineWine

‘People Don’t See You if You’re a Woman and You’re Not Really Dressed Up’: Visibility and Risk - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
Against a backdrop of research suggesting that young women are still expected to engage in active risk management on a night out (Brooks, ‘Guys! Stop doing it!’: Young women’s adoption and rejection of safety advice when socializing in bars, pubs and clubs. British Journal of Criminology, 51(4), pp. 635–651, 2011), this chapter will explore the centrality of understanding of space and visibility to young women’s negotiations of risk and safety in mainstream bars and clubs in Newcastle’s NTE. Visibility comes into play in two distinct ways here—firstly, as in the previous chapter, participants drew on narratives of ‘fitting in’, this time to describe the types of venues that felt comfortable and safe to them. Attending a venue where they felt out of place or ‘different’ to other patrons could leave women feeling exposed, visible and vulnerable, and these spaces were positioned as risky and dangerous. Secondly, women recognised that bars and clubs are spaces where ‘everyday’ experiences of heterosexualised violence are trivialised and normalised, and they managed their dress and appearance in particular ways in order to position themselves as less visible—or even invisible—to try to avoid ‘unwanted attention’ and harassment.
Keywords: Charvis; Posh People; Sexual Abuse Rape; Unwanted Attention; Working-class College Students

‘Rowdy…? That’s the Whole Point of Going on a Night Out’: Time Out, Transgression and Control - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As the previous chapter has highlighted, alcohol consumption plays an important role in the maintenance of friendships and in the individual and collective production of ‘girly’ or feminine identities in the NTE. Yet long-standing and pervasive images of alcohol consumption as a threat to femininity mean women’s negotiations of drinking continue to be fraught with tensions and ambivalences. In something of a paradox, ‘the contradictions engendered by post-feminist discourse constitute drunkenness as unfeminine, [yet] young women are enthusiastically exhorted to consume within the neoliberal culture of intoxication’ (Hutton et al. 2016: 82). In other words, to be a good, neoliberal citizen within leisure sites such as the NTE requires women to consume alcohol, yet the demands of femininity necessitate that they also show restraint. At the same time, the NTE is portrayed as a site where abandonment, hedonism and ‘rowdy’ behaviour are to an extent normalised, perhaps even encouraged, yet such behaviour ruptures traditional expectations of femininity as passive and ‘ladylike’. How do women negotiate and make sense of some of these tensions as they confront the ‘orderly disorder’ (Smith 2014: 2) of a typical night out? Is there a degree of acceptance of ‘rowdy’ or transgressive behaviour? And how does this sit alongside an expectation to be girly, as outlined in the previous chapter?
Keywords: Drinking Practices; Drunk Woman; Girly Girl; Kirsty; Transgressive Behavior

‘What Else About Her Is Fake?’: ‘Emphasised’ Femininity, Authenticity and Appearance - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
This chapter charts the ways in which young women’s negotiations of dress in the NTE are shaped by notions of visibility and authenticity and also by class. I explore the ways in which an exaggerated or emphasised mode of femininity is normalised to an extent within the NTE and highlight some of the pleasures and values young women found in their negotiations of femininity through dress, whether wholeheartedly embracing or ‘flashing’ femininity. Tensions and ambivalences are exposed as the participants both adopted and resisted elements of ‘girly’ and ‘tomboy’ identities. I then explore the ways in which forms of classed othering function to construct the feminine self in contrast to those who are perceived to lack the taste and resources to ‘do’ femininity appropriately and instead embody a somehow inauthentic and overdone performance of femininity. I briefly consider the intersections between hyper-feminine and ‘slutty’ dress, and finally explore how attempts by working-class young women to resignify a more excessive look as ‘glamorous’ may be mocked and judged beyond the local context.
Keywords: Essex Girl; Geordie; Girly Girl; Tomboy; clothingClothing

intersectionnalité - Office québécois de la langue française (Grand dictionnaire terminologique, 2019)
Cumul de différentes formes de domination ou de discrimination vécues par une personne, fondées notamment sur sa race, son sexe, son âge, sa religion, son orientation sexuelle, sa classe sociale ou ses capacités physiques, qui entraîne une augmentation des préjudices subis.
Keywords: Bibliographie; Nettoyer

Victim Services - ReadtheCode (2019)
Keywords: Nettoyer; À ajouter

Double Binds and Punchlines: An Examination of Women in Stand Up Comedy and Television Writers' Rooms - Sargent, Amberia (UCLA, 2019)
In this dissertation, I examine how double binds around sexuality and gender norms shape how women navigate sexual harassment and threats to their professional identities in stand up comedy and television writers’ rooms. I explain the ways the workplace dilemmas women confront are informed by race, sexuality, physical attractiveness, tenure, and relationship status.
Keywords: Sophie-Anne

Education in Theatrical Intimacy as Ethical Practice for University Theatre - Shawyer, Susanne; Shively, Kim (Journal of Dramatic Theory and Criticism, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël; acting; ethics; pedagogy; theatre; theatrical intimacy

Le respect de la dignité des femmes dévoilant une agression à caractère sexuel:perspectives d'intervenantes sociales et communautaires Montréalaises - Souffrant, Kharoll-Ann (Université McGill, 2019)
Publisher: McGill University
Keywords: Bibliographie; Nettoyer

Mesures de soutien et d’inclusion des personnes trans et des personnes non binaires en milieu de travail : Guide pour les employeurs et les syndicats - Table nationale de lutte contre l'homophobie et la transphobie des réseaux de l'éducation (2019)
Keywords: Bibliographie; Nettoyer

Comment aider un·e ami·e qui a eu des comportements abusifs par le passé (et qui a changé depuis) ? - Thom, Kai Cheng (Nous faire justice : Reader sur le viol et les ripostes extra-pénales, 2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

#MeToo, Time's up, and Theories of Justice - Wexler, Lesley; Robbennolt, Jennifer K.; Murphy, Colleen (I) (University of Illinois Law Review, 2019)
Keywords: Irina

La fabrique du viol - Zaccour, Suzanne (Leméac Éditeur, 2019)